Application of an Eulerian granular numerical model to an industrial scale pneumatic conveying pipeline - Heng, Jinliang (2019)
In this paper, an Eulerian granular numerical model is applied in the modelling of an industrial scale pneumatic-based cement conveying system. Steady-state simulation results are found to match pressure and outlet flowrate values with actual system data. By modifying the inlet pressure and material feed rate, data that predicts the performance of the conveying system have been obtained within the present study. Transient simulations have also been conducted and the results reveal intricate details of the cement flows along the pneumatic pipes and pipe bends. In particular, particle roping behaviour is observed to follow the sides of the wall before, during and after the pipe bends. A sloshing-like cement flow motion is also observed after the cement exits the bend. The concentration distribution of the cement particles is found not only to be partly due to gravitational effects but also the pneumatic pipe configuration. Lastly, close inspection of the secondary flows within the pneumatic pipe shows that their directional changes lead to a corresponding change in the particle roping direction, indicating that particle roping is closely associated with the secondary flow structures induced by the exact pipe configuration.